The evolution of makerspace: a review of literature - Lourenço de Jesus, Deise (2022)
This article discusses the makerspace in the context of libraries. Objective: to present definitions and evolutionary history of the makerspace in scientific literature. Method: scientific literature review. Data analysis: The definition of makerspace refers to a space for creating and sharing knowledge that emerged in the literature in 2012. It is a space derived from the Do It Yourself culture and the maker movement that has gained space within educational and industrial environments in developed countries, especially in the United States. According to the literature, it is understood that the makerspace has great educational potential that is still just beginning to be explored and could be a very important tool for the development of libraries in the near future. In Brazil, the topic is still very incipient, having little representation in the literature. Conclusions: It is a topic with potential to be developed and applied, which tends to grow nationally, if it follows the world trend. It could represent a revolutionary tool for the traditional physical space of libraries.